Frecuencias de corte en dos especies forrajeras y su efecto en las características agronómicas y rendimiento en Zungarococha, Perú – 2022 - Requejo Vasquez, Derly (2023)
The feeding of polygastrics is based on pastures and forages that should be the priority for this type of livestock in the tropics and the Faculty of Agronomy of the National University of the Peruvian Amazon looks for alternatives and presents the following work "CUTTING FREQUENCIES IN TWO FORAGE SPECIES AND THEIR EFFECT ON THE AGRONOMIC CHARACTERISTICS AND YIELD IN ZUNGAROCOCHA, PERU - 2022”. The evaluations were carried out at the 9th and 12th week of the beginning of the research work with plots of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. With a Random Complete Block Design (D.B.C.A), with five treatments and four repetitions, the treatments under study were: T1 (FC1PC22), T2 (FC1PMF), T3 (FC2PC22) and T4 (FC2PMF), where FC1= 9th week. after sowing, FC2= 12th week after sowing, PC22= Pasto Cuba 22, PMF= Pasto Maralfalfa, obtaining the following results: With the treatment FC2 P22 (12th week after sowing with Pasto Cuba 22), the achieved the best yields, which were: plant height (m) of 1.76 m., Green matter yield (Kg/m2) of 4.25 Kg/m2, Dry matter yield (Kg/m2) of 1.02 Kg /m2, in leaf length (cm) of 126.50 cm., in number of leaves of 14., in number of suckers/mat of 4.25 and yield of green matter (Kg/ha) of 42525 kg/ha.